GENETIC VARIABILITY STUDIES FOR YIELD AND YIELD COMPONENT CHARACTERS IN SAFFLOWER (CARTHAMUS TINCTORIUS L.) - MALI B B; WADIKAR P B; KHANDEBHARAD P R (Innovare Journal of Agricultural Sciences, 2025)
The field experiment was conducted with 40 genotypes of safflower at the Experimental Farm of College of Agriculture, Latur, during Rabi 2020–2021, with the purpose of exploring genetic diversity, heritability, and genetic progress for yield and yield contributing features in safflower. The presence of wide genetic variability in the experimental materials was demonstrated by an analysis of variance involving 40 safflower genotypes for ten quantitative characters, which revealed significant differences for all of the traits under study. Seed yield per plant, number of branches per plant, number of seeds per capitulum, test weight, and number of effective capitulum per plant all had a significant genotypic coefficient of variation and phenotypic coefficient of variation magnitudes. The character seed yield per plant, hull content, plant height, and test weight were similarly linked to the greatest broad sense heritability scores. The number of seeds per capitulum, number of effective capsules per plant, number of branches per plant, oil content, and days to 50% flowering were also associated with high broad sense heritability values. Characters, such as the number of branches per plant, number of effective capitulum per plant, number of seeds per capitulum, test weight, plant height, and seed yield per plant were associated with high heritability values in the broad sense, along with high expected genetic advance, indicating the role of additive genes in governing the inheritance of these traits, which could be improved through simple segregation.